Transcriptional analysis of Metalloprotease, Metallocarboxypeptidase, Isocitrate lyase, Citrate synthase, Malate synthase and Dipeptidylpeptidase V of Trichophyton rubrum isolates from dermatophytosis patients. - Datt, Shyama; Datt, Thakur; Das, Shukla; Battacharaya, Sambit Nath (Jurnal Ilmu Kesehatan dan Kesehatan, 2023)
Introduction: Dermatophytes are pathogenic fungi that cause cutaneousinfection of human and animal and grow exclusively on the stratumcorneum, nail and hair. Methods: The present study was conducted on 160 samples from clinicallydiagnosed onycomycosis patients, further subjected to culture from nailsamples of patients attending dermatology OPD of a tertiary care hospital,Delhi from January 2016 to December 2018 Results: In a soy protein culture, a substantial proteolytic activity was seen, which was secreted by Trichophyton rubrum, Trichophyton mentagrophytes and Microsporum canis. This proteolytic activity was 55–75% inhibited by O-phenanthroline, which authenticate that metalloproteases were secreted by all three species. A consensus probe was constructed on previously characterized genes, which encodes metalloproteases (MEP) of the M36 fungalysin family in Aspergillus fumigatus, Aspergillus oryzae and M. canis. From genomic libraries of T. rubrum, T. mentagrophytes and M. canis, T. rubrum & T. Mentagrophytesa five-member MEP family was isolated and also secretes MCP A & MCPB, MEP 3, MEP4, IL, CS, MS AND DPP V of the M14 family accordingto the MEROPS proteolytic enzyme database. Conclusion: This study shows that Metalloprotease, Metallocarboxypeptidase, Isocitrate Lyase, Citrate Synthase, Malate Synthase and Dipeptidylpeptidase V are expressed in Trichophyton Rubrum Isolates from Dermatophytosis Patients.